Sustainability assessments insights from multinational enterprises operating in the Philippines - Lion, Hermann; Donovan, Jerome; Topple, Cheree; Bedggood, Rowan; Masli, Eryadi K. (Abingdon, Oxon Routledge, Taylor & Francis Group, 2021)
This book looks at how multinational enterprises address sustainability within their business activities. Contextualized within a rapidly developing country in Asia, it explores how management practices, tools and techniques are implemented by foreign multinational enterprises (MNEs) operating in the Philippines. The book introduces a useful three-stage and six-step sustainability assessment framework for company practices. The three stages are framed around impact identification, impact assessment and impact monitoring, with the six steps associated with these stages, including the initiation step, scoping, impact analysis, alternative selection, monitoring and evaluation, and feedback and follow-up. The book also highlights how voluntary guidelines and global sustainability platforms play an instrumental role in directing the practices of organisations when implementing corporate sustainability.
Introduction -- Sustainability assessment research -- Issue identification and prioritisation stage -- Impact assessment stage -- Impact monitoring and follow-up stage -- Conclusion.
Includes bibliographical references (pages 187-192) and index.
Keywords: Sustainable development -- Philippines; Sustainable development reporting -- Philippines; Social responsibility of business -- Philippines; Business enterprises -- Environmental aspectS -- Philippines; International business enterprises ‡z -- Philippines; Developpement durable -- Philippines; Développement durable -- Rapports -- Philippines; Entreprises -- Responsabilité sociale -- Philippines; Entreprises -- Aspect de l'environnement -- Philippines; Entreprises multinationales -- Philippines